2018
DOI: 10.3389/fphar.2018.01228
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Neuroleukin Enhances Neuroleukin Secretion From Astrocytes and Promotes Axonal Growth in vitro and in vivo

Abstract: Under pathological conditions in the central nervous system (CNS), including spinal cord injury, astrocytes show detrimental effects against neurons. It is also known that astrocytes sometimes exert beneficial effects, such as neuroprotection and secretion of axonal growth factors. If beneficial effects of astrocytes after injury could be induced, dysfunction of the injured CNS may improve. However, a way of promoting beneficial functions in astrocytes has not been elucidated. In the current study, we focused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…Neuroleukin (NLK) is a neurotrophic factor with axonal growth activity and a product of lectin-stimulated T cells 17,18 . Previous studies showed that NLK is upregulated in the brain in patients with Huntington's disease 19 and promotes axonal growth in spinal cord injury 20 , indicating a role of NLK in neurodegenerative processes. Therefore, in the present study, we aimed to assess the potential of the inflammatory proteins MCP-1 and NLK in CSF as biomarkers for diagnosis and progression of PD and MSA.…”
Section: Introductionmentioning
confidence: 98%
“…Neuroleukin (NLK) is a neurotrophic factor with axonal growth activity and a product of lectin-stimulated T cells 17,18 . Previous studies showed that NLK is upregulated in the brain in patients with Huntington's disease 19 and promotes axonal growth in spinal cord injury 20 , indicating a role of NLK in neurodegenerative processes. Therefore, in the present study, we aimed to assess the potential of the inflammatory proteins MCP-1 and NLK in CSF as biomarkers for diagnosis and progression of PD and MSA.…”
Section: Introductionmentioning
confidence: 98%
“…Our previous study also clarified that treatment with recombinant NLK of cultured cortical neurons promoted axonal growth in the absence or presence of CSPGs. A single injection of recombinant NLK to the lesion site increased the axonal density and improved motor function in SCI mice (Tanie et al, 2018). These data reveal that the axonal growth activity of NLK may be beneficial for functional recovery in SCI.…”
Section: Introductionmentioning
confidence: 60%
“…The concentrations of NLK and antibodies were maintained at approximately 65 ng/ml in the CSF during the administration period. Our previous study demonstrated that 10-100 ng/ml NLK promoted axonal growth in cultured neurons (Tanie et al, 2018). In addition, pretreatment with 10-100 ng/ml neutralizing antibody against GRP78 diminished the axonal growth activity of NLK ( Figure 1).…”
Section: Nlk-grp78 Signaling Increases Axonal Density and Improves Momentioning
confidence: 75%
See 2 more Smart Citations